Contribution of molecular biology to the improvement of insect viruses as biological control products - Maruniak, James E. (Pesquisa Agropecuaria Brasileira, 1992)
Molecular biology has an important role in understanding biological properties of insect viruses used in biological control of insect pests. Molecular biology can also be used to improve or sustain the effectiveness of insect biocontrol products. There have been descriptions of 300 to 500 baculoviruses from various families of insects but mostly from Lepidoptera. Very few of these have been used as biocontrol products. The use of DNA restriction enzymes to characterize the genomes of baculoviruses has allowed for a precise method for identifying these different viruses. Once viruses have been identified, any contaminating virus can be detected in the preparations. These viruses may be improved by expanding the host range and virulence of baculoviruses by genetic recombination. The recombination events can be constructed and detected by molecular methodologies. Recombinant DNA techniques can also be used to modify baculoviruses in a way such that they produce bacterial or insect toxins. Such baculoviruses could kill target insects more quickly. Molecular biology methodologies are essential for quality analysis and detection of problems associated with production of insect viruses in which baculoviruses are generated with insertions of insect DNA. These transposons of DNA cause the mutant viruses to produce few polyhedra. Secondly, defective viral genomes are produced when baculoviruses are grown in continuous culture systems. Molecular biology is used to detect these and hopefully, can be used to correct these defects.